Brake friction materials - Solomon, Darius G. (Pusat Penerbitan Universiti (UPENA), Universiti Teknologi MARA, 2006)
This book contains the articles based on the papers presented in colloquims conducted by the Malaysian Brake Friction Materials Group. This book also provides enough information to Researchers and Practicing Engineers for understanding the complexities involved with developing friction materials and to learn how to produce better friction materials in the near future